Menanamkan Jiwa Kebangsaan : Peran Pendidikan Pancasila dalam Pembentukan Karakter Siswa melalui Kurikulum Merdeka - Aggi Nurhapipah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The curriculum is a guideline for learning activities that guides the educational process towards the desired results. The curriculum plays an important role in shaping the identity and national character of students within the framework of Pancasila Education. A nation’s national identity is what differentiates it from other countries, while character education aims to develop people who have high moral and ethical standards so that they can make a valuable contribution to society. The aim of this research is to find out how the independent curriculum in Pancasila education lessons is implemented in schools and determine the best way to use it to help students develop a sense of identity and national character. This research uses a qualitative method with an interview and observation approach in data collection. The research results show that, through relevant teaching strategies, Pancasila education makes a significant contribution to the internalization of ethical and national values. The findings of this study highlight how important it is to implement the independent curriculum in Pancasila education lessons optimally in order to foster the development of students’ moral character and love of their homeland. It is hoped that this research can help create more effective teaching methods for Pancasila Education.